Hypoxia- and inflammation-driven preconditioning modulates angiogenic and metabolic pathways in canine adipose-derived mesenchymal stem cells - Pablo Ocampo-Ortiz; Viviana Vallejo-Aristizabal; Marcos Gomides Carvalho; Joshua Polanco Stuart; Thaisy Dellaqua; Fernanda da Cruz Landim e Alvarenga (PLoS ONE, 2026)
The immunomodulatory properties of exogenous mesenchymal stem cells (MSCs) have been the target of research in immune-mediated diseases and organ transplants. However, the altered microenvironment decrease MSCs capabilities and survival post-transplantation. This study investigated the viability, proliferation, gene expression and proteomic of canine adipose tissue-derived MSCs (cAT-MSCs) treated with deferroxyamine [DFO] (hypoxia), interferon-γ [IFN-γ] (inflammation) or both for 48h. At 24 hours, all groups exhibited fibroblastoid morphology and adhesion to plastic, with treated groups showing greater cell spacing. After 144h, cell proliferation did not differ significantly between groups, though the treated groups had higher cell concentrations compared to the control. Gene expression analysis revealed increased Casp9 expression in the IFN-γ group, in comparison to the IFN-γ + DFO group; the FGF2 gene was upregulated in the IFN-γ group, while the DKC1 and PT53 genes showed higher expression in IFN-γ than DFO. The VEGFA was more highly expressed in the groups treated with DFO. Proteomics analysis identified 256 proteins, with 70 co-expressed across all groups, and unique proteins in each treatment group: 41 in the control, 44 in DFO, 15 in IFN-γ + DFO group, and 34 for IFN-γ. Notably, 6, 5, and 4 proteins were unique to DFO, IFN-γ + DFO, and IFN-γ treatments, respectively, when compared to the control. Preconditioning modulated angiogenic and metabolic pathways, preserving immunomodulatory function and cellular integrity. Future studies with real hypoxia and multi-omics integration will be crucial for linking molecular signatures to paracrine functions and in vivo efficacy.